Dentists’ Attitudes in Jordan towards the Shortened Dental Arch Concept: A Cross-Sectional Study - Motasum Abu-Awwad; Rula Amarin; Farah Khouli; Sirin Shaban; Sandra AlTarawneh (International Journal of Dentistry)
Aims. To assess the awareness, knowledge, attitudes, and application of the shortened dental arch (SDA) concept by dentists in Jordan. Materials and Methods. In this cross-sectional survey, a questionnaire was disseminated to a random sample of 150 dentists working in private practices, university hospitals, or governmental institutes. The chi-square (X2) test was used to examine associations. Results. One hundred and six dentists responded (70.7% response rate). Fifty-five were females. 82.1% were aware of the SDA concept. The fewer the years of experience, the more likely the dentists were aware of the SDA concept (X2, P=0.024) and the more likely they learned about it through undergraduate education (X2, P<0.001). In a hypothetical clinical situation of a patient >50 years of age with missing molar teeth, 45.3% agreed that the molars should be replaced, while 54.7% did not agree. Improving mastication was the main reason for agreeing (81.6%), while having reduced functional benefit was the main reason for disagreeing (64.9%). The treatment modality most commonly recommended was implants fixed partial dentures (84.9%). Of those aware of SDA, 67.8% agreed it could have a useful place in treatment planning within Jordan. Cost reduction for patients was the main reason for this answer, as reported by 51% of those who agreed. 26.4% did not apply SDA for any of their patients, while 50.6% applied it for <10% of their patients. Conclusion. The majority of the dentists was aware of the SDA concept and had a positive attitude towards it; however, few of them applied it in their practice.